The effect of iron deficiency anemia on experimental dental caries in mice. (September 2019) - Bahdila, Dania; Markowitz, Kenneth; Pawar, Siddhi; Chavan, Krupa; Fine, Daniel H.; Velliyagounder, Kabilan
Highlights: In a mouse model of caries, S. mutans -infected mice who had IDA developed more severe lesions than infected mice feed an iron-containing diet. Iron deficient mice lacking S. mutans were susceptible to caries as well. These results support the conclusion of observational studies reporting a relationship between early childhood caries and ID. Abstract: Objective: The objective of this study was to examine the relationship between iron deficiency and caries susceptibility in a mouse model. Materials and methods: Three-week-old C57BL/J6 mice were fed a cariogenic diet containing either standard iron (48 ppm Fe) or low iron (4 ppm Fe) levels. Concurrently, groups of mice with both diets were orally inoculated with Streptococcus mutans (1 × 10 8 ) cells on three consecutive days. At the end of the 5th week after infection, mice were sacrificed and jaws were collected for caries scoring, rating the number and severity of lesions using a modified Keyes method applicable to mice. Results: Blood analysis by the end of the 5th week revealed marked reduction in the hemoglobin and hematocrit levels of the mice fed the iron deficient diet (IDA and IDA- S. mutans ). Anemic mice in both groups lacked the incisor enamel pigmentation observed in mice fed an iron deficient diet. Anemic infected mice had the highest caries severity scores reflecting extensive deep lesions (P < 0.05). S. mutans infected mice fed a standard iron diet had similar numbers of lesions and severity scores as un-infected IDA animals (p < 0.05). IDA did not alter S. mutans CFU counts in infected animals (P < 0.05). Conclusion: These results demonstrated that IDA mice are at a higher risk of developing deep dental caries compared to non-anemic mice; highlighting the protective role of iron against dental caries.